Jaro's Persuasive Message Model in Encouraging Political Participation of New Voters Ahead of the 2024 Election Based on the Baduy Indigenous Community - Nofiasari, Wida; R, Felisianus Novandri; Rusdin, Febi Ramandhani (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The purpose of this study is to find out how Jaro's persuasive message model encourages political participation for first-time voters ahead of the Baduy Indigenous People-based 2024 elections. The theory used in this study is to use the Elaboration Likelihood Model analysis approach. This study uses a qualitative method with a case study approach where the researcher digs in depth about Jaro's persuasive message. Thus, later researchers will find a model of persuasive messages carried out by Jaro by exploring models of persuasive messages in encouraging political participation ahead of the 2024 elections based on indigenous peoples. The study results show that the Baduy people adhere to the ancestral mandate and ancestral heritage and respect the ranks of traditional leaders (Puun, Jaro Tangtu, and others) in political matters. Political outreach, prohibition of campaigning, and freedom of choice are forms of effective persuasive communication for the Baduy people. The principles of neighborhood, religion, and household are very closely attached to the daily life of the Baduy people. The Baduy Dalam community uses the central route with a critical and careful mind in receiving information and political messages. Baduy Luar people easily receive information and do not think critically about information and political messages. This study concludes that the political and democratic awareness of the Baduy indigenous people continues to increase. Persuasive communication is carried out by Jaro subtly through political socialization and spiritual beliefs that live in Baduy customs. Elaboration Model Likelihood is implemented through cognitive (knowledge and experience), affective (acceptance and rejection), and connotative (action). The Baduy Dalam people receive messages through the central route and the Baduy Luar people use the peripheral route.